AN OVERVIEW OF PHYSICAL ACTIVITY IN ELEMENTARY SCHOOL A BIBLIOMETRIC ANALYSIS - Karisman, Vicki Ahmad; Kuswahyudi, Kuswahyudi; Setiakarnawijaya, Yasep; Taufik, Muhamad Syamsu; Kastrena, Ervan; Solihin, Amril Rahmat; Rahadian, Adi; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
The study purpose was Our reviews make some unique contributions. First, we identify authors whose publications can serve as benchmarks for the future of researchers, geographic coverage of "physical activity" issues AND "element school", and the most relevant journals cited papers. Materials and methods Research using bibliometric analysis methods on physical activities in elementary schools has never been conducted, especially in Accredited International journals. This study evaluated the pattern and development of physical activity in elementary schools in 2013-2021. Materials and methods. This study used bibliometric analysis and similarity visualization using the VOS- Viewer application for graphical conception of bibliographic very such as keywords and co-authoring. In addition, this study will also evaluate, author country organizations, developments in various countries, the most prolific authors, the most cited citations, and the level of author collaboration. Results. The results showed “physical activity" AND "element school" has grown significantly demonstrated a considerable increase in publications on "physical activity" AND "elementary school" over the previous nine years. Many publications in the globe with primary authors and research institutes participating are from the United States, which is the world leader in the study of physical activity in elementary schools. Conclusions: The Journal of School Health is a prestigious journal. According to a keyword analysis, studies on "physical activity" AND "element school" have concentrated on topics linked to physical exercise, kids, and elementary school over the past 20 years. Conclusions. The bibliometric analysis presented provides relevant information about the main themes studied about "physical activity" AND "elemental school". and technological advances in development.